2021
DOI: 10.3389/fpubh.2021.591439
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Single and Combined Contributions of Home-Grown Supply and Health Literacy on Fruit and Vegetable Consumption: An Empirical Exploration in Rural India

Abstract: Low fruit and vegetable consumption (FVC) remains a global health challenge. Fostering subsistence agriculture through the production and home-grown consumption (HGC) of fruits and vegetables are seen as potential strategies for improving overall FVC, in particular, for developing countries like India. In addition, educational strategies targeting FVC health literacy are also used. Little evidence has documented a connection between these two strategies. We examine the single and combined influence of HGC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In addition to general and post-secondary education, targeted nutrition education programs (e.g., skills training) have found prior success in boosting vegetable consumption ( 137 , 138 ). Health literacy programs have also demonstrated positive impact on fruit and vegetable ( 139 ) and, when paired with agricultural intervention programs (e.g., home gardening education), greater synergies can be achieved ( 67 , 69 ). However, the insights from this study also point to a need for curriculum expansion, with more precise messaging and content on processed vegetables, to better equip consumers with the information needed to make trade-offs and decisions regarding substitutions given their time and monetary limitations ( 140 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to general and post-secondary education, targeted nutrition education programs (e.g., skills training) have found prior success in boosting vegetable consumption ( 137 , 138 ). Health literacy programs have also demonstrated positive impact on fruit and vegetable ( 139 ) and, when paired with agricultural intervention programs (e.g., home gardening education), greater synergies can be achieved ( 67 , 69 ). However, the insights from this study also point to a need for curriculum expansion, with more precise messaging and content on processed vegetables, to better equip consumers with the information needed to make trade-offs and decisions regarding substitutions given their time and monetary limitations ( 140 ).…”
Section: Discussionmentioning
confidence: 99%
“…The agri-food supply chain, in turn, operates as a complex system spanning from input of raw materials, to farming, processing, packaging, and distribution (65). Physical accessibility also extends to the point of market access, where factors like having car access or grocery/food retail outlets within the neighborhood, supermarket choice, and access to homegrown produce via a home or community garden influence FVC (14,51,66,67). For adults, FVC can also be mediated by consumption of fruits and vegetables from home gardens or farms (66)(67)(68)(69).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of traditional practices, the participants in this study also reported cultivating and consuming own vegetables and grains. Surendran et al and Auma et al found that consumption of home-grown food and access to home gardens enabled the consumption of healthier fruit and vegetables with lower environmental impact [38,39]. Therefore, household cultivation in rural areas should be preserved and promoted, which could potentially be an effective strategy for reversing the declining trend of vegetable consumption in rural China.…”
Section: Traditional Food Views and Practices With Both Beneficial An...mentioning
confidence: 99%